Metode Istinbath KH. Muhammad Sarni Al-Alabi Tentang “Sanda Perjanjian Dengan Akad Jual Putus” Dalam Kitab Mabâdi Ilm Al-Fiqh - Aisyah, Lisda; Prasetya, Teguh Eka; Firdaus, Muhammad Irkham (Universitas Darussalam Gontor, 2023)
**English**This study is motivated by the thoughts of K.H Muhammad Sarni al-Alabi about the permissibility of the person receiving the pledge to take advantage of the pawned goods with the term